The Singapore Story (vol. l) : From Third World to First ; The Singapore Story (vol. 2) : 1965-2000, por Lee Kuan Yew, Singapore : Singapore Press Holdings, 1998-2000 - Wilhelmy von Wolff, Manfred (Estudios Internacionales, 2002)
-